Does Allergy Break Bones? Osteoporosis and Its Connection to Allergy - Sirufo, Maria Maddalena; Suppa, Mariano; Ginaldi, Lia; De Martinis, Massimo (International journal of molecular sciences, 2020)
Osteoporosis and allergic diseases are important causes of morbidity, and traditionally their coexistence has been attributed to causality, to independent processes, and they were considered unrelated. However, the increasing knowledge in the field of osteoimmunology and an increasing number of epidemiological and biological studies have provided support to a correlation between bone and allergy that share pathways, cells, cytokines and mediators. If the link between allergic pathology and bone alterations appears more subtle, there are conditions such as mastocytosis and hypereosinophilic or hyper-IgE syndromes characterized by the proliferation of cells or hyper-production of molecules that play a key role in allergies, in which this link is at least clinically more evident, and the diseases are accompanied by frank skeletal involvement, offering multiple speculation cues. The pathophysiological connection of allergy and osteoporosis is currently an intriguing area of research. The aim of this review is to summarize and bring together the current knowledge and pursue an opportunity to stimulate further investigation.